The professionalization of early childhood education, care educators and pedagogical coordinators: a key issue of adult education - Silva, Clara (Form@re - Open Journal per la formazione in rete, 2019)
This paper focuses on the issue of in-service training of personnel involved in Early Childhood Education and Care (ECEC), in light of the most recent European and Italian studies and regulations and in line with the principles of lifelong learning and adult education. The paper then illustrates the main aspects of a survey of the literature on in-service training of ECEC personnel, indicating the most significant experiences in Italy. Finally, as an example of good in-service training practices at university level, the case of the Master in “Pedagogical coordination of early childhood education and care services” of the University of Florence is described, together with some reflections on the role and function of the figure of the pedagogical coordinator, also as a promoter of in-service training of ECEC personnel. La formazione degli educatori di nidi e servizi prima infanzia e dei coordinatori pedagogici: un tema chiave della formazione degli adulti L’articolo affronta il tema della formazione in servizio del personale della Early Childhood Education and Care (ECEC), alla luce degli studi e delle normative europee e italiane più recenti, nella prospettiva dei principi dell’educazione permanente e degli adulti. Presenta poi gli aspetti salienti di un’analisi della letteratura sulla formazione in servizio del personale dell’ECEC e indica le più significative esperienze realizzate sul territorio italiano. Infine, come esempio di buone pratiche di formazione in servizio a livello universitario, riporta il caso del Master in “Coordinamento di nidi e servizi per l’infanzia zero-sei anni” dell’Università degli Studi di Firenze, insieme ad alcune riflessioni sul ruolo e sulla funzione della figura del coordinatore pedagogico, anche come promotore della formazione in servizio del personale dell’ECEC.